Influence of Removable Orthodontic Appliance on Oral Microbiological Status - Jabur, Saba Fouad (Journal of the Faculty of Medicine Baghdad, 2008)
Background: the placement of orthodontic appliances creates a favorable environment for the accumulation of microbiota, therefore this study is to assessthe relationship between removable orthodontic appliance and oral microflora.Materials and methods: a sample 45 patients who come to orthodontic department at the collage of dentistry/Baghdad university, divided into 3 groups:group 1 (15) without appliance, group2 (15) with appliance for 2 weeks-2 months, and group 3 (15) with appliance for 2 -4 months, then examine the oral microfloraand compared between the 3 groups.Results: the result showed eleven types of microorganisms appear in group 3 then followed by seven types in group 2 but only three types of microorganisms ingroup 1.Conclusion: there is need to educate the patients who received orthodontic appliance about their oral hygiene because oral microflora were changed amongorthodontic patients.